HUBUNGAN JUMLAH LEUKOSIT DENGAN KADAR C REAKTIF PROTEIN PADA PENDERITA FEBRIS - Soejat, Endriana (THE JOURNAL OF MUHAMMADIYAH MEDICAL LABORATORY TECHNOLOGIST)
HUBUNGAN JUMLAH LEUKOSIT DENGAN KADAR C REAKTIF PROTEIN PADA PENDERITA FEBRIS dr. Endriana Soedjat, Sp. PK.Prodi D3 Analis Kesehatan UM Surabaya AbstractLeukocyte is a unit of the bodys defense system that serves to protect the body against the entry of foreign objects. One of the causes of the increased number of leukocytes due to the entry of bacteria in the body marked increase in the number of leukocytes neutrophils or polymorphonuclear leukocytosis (netrofilia). C Reactive Protein is one of the acute phase protein levels in the blood is increased in acute infection as non-specific immune response by binding to various microorganisms. C Reactive Protein measurement used to assess the activity of inflammatory diseases. n some cases where the number of leukocytes increased while the C Reactive Protein levels normally make the clinician asks for re-examination. Accordingly, this study was conducted by taking a formulation of the problem "Is there a relationship with a number of leukocytes Reactive Protein C levels in patients with febrile" This research is correlational aimed to determine the relationship of the number of leukocytes and levels of C reactive protein in patients with febrile symptoms in Hospital Surabaya Family Partners for 211 patients. This study was conducted from January to June 2011. Based on the results of the chi square test for leukocyte counts and levels of C Reactive Protein, obtained significant level of 22.57 which showed no correlation with the number of leukocytes Reactive Protein C levels in patients with febrile symptoms.Keyword : leukocyte, C reactif protein